Comparing ICT components in MLISc. curriculum of TU with SAARC Universities - Nyoupane, Bhabana; Nyaichyai, Lila (Access: An International Journal of Nepal Library Association, 2022)
The study, entitled "Comparing ICT components in MLISc. curriculum of TU with SAARC Universities," has an objective to identify the differences and similarities of MLISc., TU courses in entailing ICT contents. To obtain this objective, this study compares the ICT content of the MLISc. curriculum of TU with five universities from India, Pakistan, Sri Lanka, and Bangladesh, one from each country. Those universities were selected with reference to the higher rank recommended by website Unirank 2021. The sources of data were interpreted categorically based on syllabus content. As the result, the comparison clarified that the MLISc. curriculum of TU has incorporated similar standards of those selected universities, where fundamentals of ICT, data communication and networking, programming language, library management software, web designing, multimedia, and information retrieval courses are incorporated. In MLISc., TU courses, the content related to library management software are relatively less. However, to address the gap, Central Department of Library and Information Science, (CDLIS) TU has included a practical class on Koha, LIS from 2019. More up-to-date, comprehensive package of library automation and digitization services, from operations to system design, is the most demanding from LIS graduates, practical-based courses incorporated into LIS education would be preferable for increasing the effectiveness of ICT in LIS management.